2017
DOI: 10.3892/mmr.2017.7884
|View full text |Cite
|
Sign up to set email alerts
|

Dysifragilone A inhibits LPS‑induced RAW264.7 macrophage activation by blocking the p38 MAPK signaling pathway

Abstract: Dysifragilone A, a sesquiterpene aminoquinone based on a rearranged avarone skeleton, has been previously isolated and identified from the South China Sea sponge Dysidea fragilis. In the present study, anti‑inflammatory activity and the underlying molecular mechanism of dysifragilone A were studied using the classical inflammation model of lipopolysaccharide (LPS)‑activated RAW264.7 macrophage cells and an MTT assay, Griess method, ELISA and western blotting were used. The results revealed that dysifragilone A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…TNF-α is an effective cytokine that stimulates the inflammation mechanism and triggers various inflammatory diseases [ 69 ]. IL-6 is excreted by several cells in response to the inflammation process and plays a critical pathological role in autoimmunity and chronic inflammation [ 70 , 71 , 72 ]. Several studies have shown that the expression of IL-6 and TNF-α is dramatically upregulated in cells treated with LPS [ 73 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…TNF-α is an effective cytokine that stimulates the inflammation mechanism and triggers various inflammatory diseases [ 69 ]. IL-6 is excreted by several cells in response to the inflammation process and plays a critical pathological role in autoimmunity and chronic inflammation [ 70 , 71 , 72 ]. Several studies have shown that the expression of IL-6 and TNF-α is dramatically upregulated in cells treated with LPS [ 73 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…33 The membrane was blocked with 5% nonfat dry milk (Sigma) in TBST buffer for 1 hour at room temperature. The total protein in cell extracts was quantified with the Bradford assay (Bio-Rad).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Thirty micrograms of protein from each sample was separated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and then transferred to a polyvinylidene difluoride membrane as previously described. 33 The membrane was blocked with 5% nonfat dry milk (Sigma) in TBST buffer for 1 hour at room temperature. Primary antibodies against CD36 (1:1000, CST, Boston, MA) or ADAM22 (1:1000, Abcam, Cambridge, MA) and β-actin (1:10 000; CST) were added and t incubated overnight at 4°C.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…The RAW264.7 cells were used to evaluate the anti-inflammatory activity of compounds 1 – 3 following a literature procedure [ 36 ]. The cells were seeded in 96-well plates at a density of 5 × 10 5 cells/mL.…”
Section: Methodsmentioning
confidence: 99%